(untitled) (INTERNATIONAL CONFERENCE ON MEDICINE, SCIENCE, AND EDUCATION, 2026)
This article discusses the process of synthesizing antibiotics from microorganisms, their biological significance, and the possibilities of their industrial application. The study specifically analyzes bacteria belonging to the Acremonium chrysogenum, Streptomyces genera, and their role in the synthesis of beta-lactam antibiotics (Cephalosporin C, Ceftriaxone sodium, Azobact). The article consistently describes the fermentation process, the formation of 7-aminocephalosporanic acid (7-ACA) from Cephalosporin C, as well as the stages of the production of Ceftriaxone sodium through chemical modification. The results of the study show that the production of antibiotics based on microorganisms is not only an economically affordable, but also an environmentally safe and highly efficient biotechnological route. This approach can also serve as the main source for the creation of new types of antibiotics in the future.